Four Flaws: Reflections on the Canadian Approach to PrivateInternational Law - Hume, Nathan (Canadian Yearbook of International Law/Annuaire canadien de droit international, 2007)
This article traces the evolution of the Canadian approach to privateinternational law from Morguard Investments Ltd. v. De Savoye to Castillo v. Castillo and identifiesfour major flaws that have significant implications for both privateinternational law and Canadian federalism: (1) ambiguous and inconsistentterminology that undermines the conceptual foundation of this approach whileobscuring its potential impact; (2) the Court’s use of American conflict oflaws jurisprudence to reinforce a deferential orientation in Canadianprivate international law; (3) the Court’s vision of the international orderand understanding of public international law, which has begun to affect theCanadian federal system; and (4) the model of the Canadian Constitutionemployed in these cases, which may have broad negative consequences forprovincial interests. The article argues that these flaws are remediable,that both constitutional text and recent opinions contain resources usefulto this end, and that, however the Court decides to address these problems,subsequent iterations of the Canadian approach to private international lawshould emphasize clarity, consistency, and comprehensiveness., Sommaire Cet article trace l’évolution de l’approche canadienne au droitinternational privé à partir de Morguard Investments Ltd. c. De Savoye jusqu’à Castillo v. Castillo. Il cernequatre défauts majeurs qui ont des conséquences significatifs tant pour ledroit international privé que pour le fédéralisme canadien, dont: (1)l’emploi d’une terminologie ambiguë et contradictoire qui mine lesfondements conceptuels de cette approche tout en déguisant son impactpotentiel; (2) l’utilisation par la Cour de la jurisprudence américaine enmatière de droit international privé pour justifier une orientationdéférentielle en droit international privé canadien; (3) la vision de laCour de l’ordre international et sa compréhension du droit internationalpublic, qui ont des effets sur le système fédéral canadien; et (4) le modèlede la constitution canadienne révélée dans ces cas, qui pourrait avoir desérieux effets négatifs sur les intérêts provinciaux. L’article affirme queces défauts peuvent être rémédiés, que les textes constitutionnels et desopinions récentes révèlent des ressources utiles à cette fin, et que, peuimporte la façon dont la Cour s’y prend pour adresser ces problèmes,l’approche future du Canada au droit international privé doit avant toutêtre claire, uniforme et compréhensive.